Oral-Facial-Digital Syndrome Type IX with Subfoveal Drusenoid Deposit - You, Jong In; Bang, Seul Ki; Yu, Seung-Young; Jin, Kyung Hyun (Journal of Pediatric Genetics, 2020)
We describe a patient with oral-facial-digital syndrome (OFDS) with the following anomalies: cleft lip, cleft palate, micrognathia, hypertelorism, nasal septum deviation, thumb polydactyly in the right hand, and partial agenesis of the corpus callosum. In addition, the patient had optic disc coloboma in the left eye and subfoveal drusenoid deposit in the right eye, features of OFDS type IX. Subfoveal drusenoid deposit has not been previously reported in OFDS type IX. Evaluation of the fundus is necessary for diagnosis of OFDS.
Keywords: oral-facial-digital syndrome; oral-facial-digital syndrome type IX; coloboma; subretinal drusenoid deposit